2015
DOI: 10.1016/j.fertnstert.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial pattern, but not endometrial thickness, affects implantation rates in euploid embryo transfers

Abstract: Objective To evaluate the relation of endometrial thickness (EnT) and endometrial pattern (EnP) to euploid embryo transfer (ET) outcomes. Design Retrospective cohort Setting Private academic clinic Patients Patients (n=277, 36.1±4.0 years) whose embryos (n=476) underwent aneuploidy screening with fresh (n=176) or frozen (n=180) ET from July 2010–March 2014. Interventions EnT and EnP were measured on trigger day and at ET. Patients were stratified by age and cycle type (fresh or frozen). Cycle data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 86 publications
2
75
1
4
Order By: Relevance
“…In a retrospective observational study, an endometrial thickness of 9-14 mm on the day of progesterone supplementation was associated with significantly higher implantation and pregnancy rates compared with an endometrial thickness of 7-8 mm [73]. However, neither endometrial thickness nor endometrial pattern had any impact on implantation and pregnancy rates following euploid blastocyst transfer [74].…”
Section: Discussionmentioning
confidence: 92%
“…In a retrospective observational study, an endometrial thickness of 9-14 mm on the day of progesterone supplementation was associated with significantly higher implantation and pregnancy rates compared with an endometrial thickness of 7-8 mm [73]. However, neither endometrial thickness nor endometrial pattern had any impact on implantation and pregnancy rates following euploid blastocyst transfer [74].…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have documented that the endometrial thickness was not associated with implantation and clinical pregnancy rates on the day of fresh and frozen embryo transfer [58]. However, the study by Zhao et al [59] suggested that pregnancy was unlikely to occur when the endometrial thickness was <6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[57] изучали влияние толщины и структуры эндометрия на исхо-ды переносов свежих и размороженных эуплоидных эмбрионов после преимплантационной генетиче-ской диагностики. Авторы не выявили зависимости между частотой имплантации, частотой наступления клинической беременности и толщиной эндометрия в день переноса эмбрионов.…”
Section: нужно ли дополнительно назначать эстрогены пациенткам с тонкunclassified